MANAJEMEN HUBUNGAN SEKOLAH DENGAN MASYARAKAT: MEMPERKUAT MUTU PENDIDIKAN MELALUI KEMITRAAN KOLABORATIF - Eva Nurjanah; Futihat Amini; Ratu Zulaikha; Velayati Zuraida (Jurnal Manajemen Pendidikan, 2026)
School-community relationship management is an important aspect of educational management that contributes to improving educational quality through community participation and strategic partnerships. This study aims to analyze the concepts, principles, implementation strategies, challenges, and contributions of school-community relationship management in improving educational quality. The research employed a qualitative literature review approach. Data were collected from 35 national and international scientific journal articles published between 2021 and 2026, sourced from Google Scholar, Garuda, DOAJ, and Scopus databases. The data were analyzed using content analysis through the stages of identification, selection, classification, synthesis, and interpretation of previous research findings. The results indicate that school-community relationship management positively contributes to educational quality improvement through increased community participation (30%), effective communication (25%), partnership strengthening (20%), school transparency and accountability (15%), and the utilization of information technology (10%). Effective management of school-community relationships enhances public trust, expands educational resource support, strengthens school governance, and improves the quality of educational services. However, its implementation still faces several challenges, including low community participation, communication barriers, and suboptimal use of digital technology.